DEFORMATION-WAVE ASPECT OF FATIGUE FAULT OF SURFACE LAYERS OF PARTS UNDER FRICTION AND WEAR - Маліновський, Юрій; Цвіркун, Сергій; Міненко, Роман; Власенков, Дмитро; Дворецький, Дмитро; Рибак , Д. П.; Терешина, С.С.; Олійник, Світлана (Problems of Friction and Wear, 2022)
Modern requirements for the reliability and durability of operated and designed machines require the improvement of methods for calculating friction and wear for them. To assess the friction conditions and wear resistance of parts, geometric, molecular, deformation and combined theories are mainly considered. However, during the interaction of parts, deformation processes often take place, which manifest themselves in the form of corrugated surfaces with curves close to sinusoids in cross sections. The amplitudes of the resulting sinusoids can be considered as formed deformation microroughnesses, and the sizes of these microroughnesses can be comparable with geometric microroughnesses, and sometimes they can exceed them. Such additional (unaccounted for) roughness should be studied when performing calculations for friction and wear. However, no such theory has been developed so far. Therefore, we set the task to create the prerequisites for the development of the theory of friction and wear, taking into account the deformation-wave processes when a flat stamp or a rolling roller moves along a half-plane. To formulate the problem, the deformation processes occurring in the thin surface layers of the stamp and workpiece are considered. With such a formulation of the problem, a thin surface layer of a half-space either loses its stability and receives wave-like deformations, or the surface layer is under the influence of cyclic loading. In both cases, wear and chipping of the contacting surfaces occurs. In general, taking into account the indicated features of the friction and wear processes, the area of all protrusions on each of the contacting bodies can change significantly, and the height of the largest microroughnesses can also change. For the correct calculation of the degree of wear of the surfaces under consideration, it is necessary to correct the data on the area of the protrusions of the contacting bodies, and the height of the largest microroughnesses. The paper also provides for the possibility of taking into account the increase in the equivalent voltage , due to the increase in the speed of mutual sliding of parts V, by introducing the dynamic coefficient into the calculations.